Athletes` perception of parental support and its influence in sports accomplishments - A retrospective study - Siekanska, M. (Human Movement, 2012)
The main purpose of this study was to investigate the effect of family environmental factors on student athletes featuring different levels of sports accomplishment: 1) a low level - no significant achievements (N = 46), 2) a medium level - significant achievements at a regional level (N = 86) and 3) a high level - significant achievements at national and/or international level (N = 33). Methods. The participants were administered a demographic survey and the Athletes` Family Environment Questionnaire (AFEQ). Results. One-way ANOVA found that the high achievers` families differ from the medium- and low-level achievers in five (out of nine) of the studied family environment factors: children as an important value in family life, sport as an important value in family life, parents` involvement in their child`s sports career, the overall genetic-environmental conditioning of their child`s talent and passion for sports, as well as parents living through their child`s involvement in sports. Conclusions. Such factors as parents` involvement in their child`s sports career and parents living through their child`s involvement in sports are especially interesting for researchers. On one hand, these factors can be beneficial (providing instrumental support, spectatorship), but on the other hand, they can have adverse effects such as a child quitting sports, experiencing burnout or have a higher risk of injury. From a practical perspective, the family environment may be the most accessible as well as the most important of the socio-environmental dimensions of young athletes.